2022
DOI: 10.3390/ijms23126599
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, Characterization and the Commercialization of Elite Rhizobia Strains in Africa

Abstract: Grain legumes play a significant role in smallholder farming systems in Africa because of their contribution to nutrition and income security and their role in fixing nitrogen. Biological Nitrogen Fixation (BNF) serves a critical role in improving soil fertility for legumes. Although much research has been conducted on rhizobia in nitrogen fixation and their contribution to soil fertility, much less is known about the distribution and diversity of the bacteria strains in different areas of the world and which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 182 publications
0
5
0
Order By: Relevance
“…Field co-inoculation trials with endophytic nitrogen-fixing bacteria in MLI systems, such as Bradyrhizobium elkanii , Bradyrhizobium liaoningense , Bradyrhizobium yuanmingense , and Sinorhizobium fredii , have been attributed to the promotion of plant growth by enhancing resource uptake, nitrogen fixation, nodulation, chlorophyll synthesis, and contribute to soil fertility 68 . These ecological services can contribute to improving soil fertility and decreasing reliance on synthetic chemical fertilizer inputs.…”
Section: Discussionmentioning
confidence: 99%
“…Field co-inoculation trials with endophytic nitrogen-fixing bacteria in MLI systems, such as Bradyrhizobium elkanii , Bradyrhizobium liaoningense , Bradyrhizobium yuanmingense , and Sinorhizobium fredii , have been attributed to the promotion of plant growth by enhancing resource uptake, nitrogen fixation, nodulation, chlorophyll synthesis, and contribute to soil fertility 68 . These ecological services can contribute to improving soil fertility and decreasing reliance on synthetic chemical fertilizer inputs.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of Bradyrhizobium in Desmodium species root-nodules is noteworthy, considering its well-documented robust nitrogen-fixing capability in legumes within tropical and subtropical regions (Hurse and Date, 1992 ). This genus is a common microsymbiont in major pulses like soybean ( Glycine max ), peanuts ( Arachis hypogaea ), common bean ( Phaseolus vulgaris ), cowpea ( Vigna unguiculata ), and lima beans ( Phaseolus lunatus ) (Ormeño-Orrillo and Martínez-Romero, 2019 ; Muthini et al, 2020 ), with reported associations in various regions, including sub-Saharan Africa (Wekesa et al, 2022 ), China (Gu et al, 2007 ), Argentina (Toniutti et al, 2017 ) and Mexico (Parker, 2002 ). Our findings, however, differ from a study by Xu et al ( 2016 ), which highlighted a higher occurrence of fast-growing rhizobia isolates ( Rhizobium, Mesorhizobium , and Pararhizobium spp.)…”
Section: Discussionmentioning
confidence: 99%
“…Plants cannot assimilate nitrogen, the primary limiting nutrient in agriculture, due to their inability to break down existing complex bonds (Oldroyd, 2013 ). However, rhizobia colonizes legume plant roots, forming an endosymbiotic relationship that ensures nitrogen is converted to ammonia via biological nitrogen fixation (BNF) (Jalloh et al, 2020 ; Wekesa et al, 2022 ). This happens in specialized organs known as root-nodules, which are formed via an intricate association with rhizobia (Oldroyd, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of Bradyrhizobium in Desmodium species root-nodules is noteworthy, considering its well-documented robust nitrogenfixing capability in legumes within tropical and subtropical regions (Hurse and Date, 1992). This genus is a common microsymbiont in major pulses like soybean (Glycine max), peanuts (Arachis hypogaea), common bean (Phaseolus vulgaris), cowpea (Vigna unguiculata), and lima beans (Phaseolus lunatus) (Ormeño-Orrillo and Martínez-Romero, 2019; Muthini et al, 2020), with reported associations in various regions, including sub-Saharan Africa (Wekesa et al, 2022), China (Gu et al, 2007), Argentina (Toniutti et al, 2017) and Mexico (Parker, 2002). Our findings, however, differ from a study by Xu et al (2016), which highlighted a higher occurrence of fast-growing rhizobia isolates (Rhizobium, Mesorhizobium, and Pararhizobium spp.)…”
Section: Discussionmentioning
confidence: 99%
“…Plants cannot assimilate nitrogen, the primary limiting nutrient in agriculture, due to their inability to break down existing complex bonds (Oldroyd, 2013). However, rhizobia colonizes legume plant roots, forming an endosymbiotic relationship that ensures nitrogen is converted to ammonia via biological nitrogen fixation (BNF) (Jalloh et al, 2020;Wekesa et al, 2022). This happens in specialized organs known as root-nodules, which are formed via an intricate association with rhizobia (Oldroyd, 2013).…”
Section: Introductionmentioning
confidence: 99%